PERSEPSI MAHASISWA BIMBINGAN DAN KONSELING TERHADAP KINERJA GURU BIMBINGAN DAN KONSELING - Olimpia Babtista; Renatha Ernawati; Eustalia Wigunawati (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
ABSTRACT This study aims to describe how the perceptions of the counseling students towards the performance of the guidance and counseling teachers. As with the phenomenon on November 12, 2019, the Twitter social network was stirred up by the discussion about